Maqashid Al-Sharia in the Contemporary Era's Reinterpretation of Islamic Inheritance Distribution - M. Waritsul Firdaus. F (Universitas Muhammadiyah Yogyakarta, 2023)
In this research, the author explores the principles of Maqashid al-Syariah, which are the universal goals and values in Islamic law. These principles help interpret the teachings of Islam in modern and diverse contexts, including in inheritance law issues. The concept of inheritance law in Islam, especially the division between men and women, is also deeply discussed. Contemporary views that support gender equality in inheritance distribution challenge traditional interpretations that acknowledge the difference in shares between men and women. This argument emerges from the perspective that the role and economic contribution of women in society have changed over time. However, some scholars argue that the principles of Islam, which are included in qath'i (certain) evidence, such as the division of 2:1, cannot be altered in certain situations.